Serum amylase level measurement in acute abdominal pain - Abdullah Hawramy, Taher; Ahmed Mohammed, Dara; H. Tahir, Botan (Kurdistan Journal of Applied Research, 2019)
Acute abdominal pain is a frequent symptom to the emergency department, can be caused by various pathologic processes. The aim of this study was to appraise the role of serum amylase level in diagnostic workup of non-traumatic adult patients presented with acute abdominal pain to surgical emergency department (ED). Our study is based on data collected retrospectively from patients’ medical records admitted to Shar Emergency Surgical Unit, Sulaimani, Iraq from 10th January 2019 to 20th May 2019. All non-traumatic adult patients with acute abdominal pain within twenty-four hours before admission were included and serum amylase levels were measured on admission using Enzyme-Linked Immunosorbent Assay (ELISA) available at (ED). Overall, 68 patients were included, with mean age of 45.9 years over the aforementioned time period, 44 females (64.7%) and 24 males (35.3%), of which 37 patients had normal serum amylase level (14 male and 23 female patients), defined as levels between (35 IU/L-115 IU/L) by the laboratory (ELISA) device used for all the tests, while the other 31 patients (10 males and 21 females) had high serum amylase levels due to different disease processes, the most common two with equal frequencies were acute calculous cholecystitis (41.9%) and acute pancreatitis (41.9%). Elevated serum amylase levels can be observed with several medical and surgical problems in patients with acute abdominal pain, but high values are usually associated with acute inflammatory pancreatic and gallbladder conditions, with very high levels in the former, making it one of the important diagnostic tools that can be used by health-care providers when evaluating patients suspected to have acute pancreatitis or acute calculous cholecystitis.